2018
DOI: 10.1111/biom.12870
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Model for Helices with Applications

Abstract: Motivated by a cutting edge problem related to the shape of α -helices in proteins, we formulate a parametric statistical model, which incorporates the cylindrical nature of the helix. Our focus is to detect a "kink," which is a drastic change in the axial direction of the helix. We propose a statistical model for the straight α -helix and der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Dickerson and Geis (1969) give a value of 1.75 radians = 100.3 • . Recent confirmation can be obtained from the detailed analysis of the maximum likelihood estimation of β carried out for 129 straight helices from crowdsourcing data in the web supplement (Web Figure 5( Mardia et al (2018); for this data it was found that the mean estimate of β is 99.1 • with a standard error of 1.2 • .…”
Section: S11mentioning
confidence: 70%
See 4 more Smart Citations
“…Dickerson and Geis (1969) give a value of 1.75 radians = 100.3 • . Recent confirmation can be obtained from the detailed analysis of the maximum likelihood estimation of β carried out for 129 straight helices from crowdsourcing data in the web supplement (Web Figure 5( Mardia et al (2018); for this data it was found that the mean estimate of β is 99.1 • with a standard error of 1.2 • .…”
Section: S11mentioning
confidence: 70%
“…Alfahad et al In more detail, the paper is organized as follows. Section 2 introduces the statistical helix model (similar in spirit to Mardia et al (2018), but more geometrically explicit). Section 3 gives the details behind the optimized least squares algorithm.…”
Section: S9mentioning
confidence: 99%
See 3 more Smart Citations